Measuring experiences of restrictiveness in forensic psychiatric care: developing a questionnaire - Tomlin, Jack (2021)
Forensic psychiatric care is often practiced in closed institutions. These highly regulated, secure and proscriptive environments can reduce autonomy, self-expression and personhood. Taken together these settings can feel restrictive as patients’ active participation in clinical, organizational, community and personal life-worlds are curtailed.